Functional Role of G9a Histone Methyltransferase in Cancer - Casciello, Francesco; Windloch, Karolina; Gannon, Frank; Lee, Jason S. (Frontiers in Immunology, 2015)
Post-translational modifications of DNA and histones are epigenetic mechanisms which affect the chromatin structure, ultimately regulating gene expression. Different epigenetic enzymes are actively involved in the addition or the removal of various covalent modifications which include acetylation, methylation, phosphorylation, ubiquitination and sumoylation. Deregulations of these processes are a hallmark of cancer. For instance, G9a, a histone methyltransferase responsible for histone H3 lysine 9 (H3K9) mono- and di-methylation, has been observed to be upregulated in different types of cancer and its overexpression has been associated with poor prognosis. Key roles played by these classes of enzymes in various diseases have led to the hypothesis that these molecules represent valuable targets for future therapies. In this topic, a number of small molecule inhibitors have been developed to specifically block the epigenetic activity of these enzymes, representing promising therapeutic tools in the treatment of human malignancies, such as cancer. In this review, the role of one of these epigenetic enzymes, G9a, is discussed, focusing on its functional role in regulating gene expression, as well as its implications in cancer initiation and progression. We also discuss important findings from recent studies using epigenetic inhibitors in cell systems in vitro as well as experimental tumor growth and metastasis assays in vivo.